UJI ANTIBAKTERI Virgin Coconut Oil DARI BERBAGAI MEREK TERHADAP BAKTERI Staphylococcus aureus dan Enterococcus faecalis - Ulfayani Mayasari; Alfi Sapitri; Sri Maulida Putri (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2020)
Virgin Coconut Oil (VCO) has the ability as an antivirus, antibacterial and antifungal, it is due to the content of lauric acid, caprylic acid, Staphylococeus aureus and Enterococcus faecalis are bacteria that act as normal flora in the human body. If it exceeds a certain limit, both of these bacteria can become pathogens. The purpose of this study is to find out Virgin Coconut Oil from various brands can inhibit the growth of Staphylococcus aureus and Enterococcus faecalis.Antibacterial power test is done by the diffusion method to use the cylinder cup, and antibacterial power measured by the diameter of the urea inhibiting microbial growth by using a caliper. Antibacterial test results for Staphylococeus aureus bacteria on brand â€œAâ€ (96.3 mm), brand â€œBâ€ (10.3 mm), brand â€œCâ€ (11 mm).The average brand â€œDâ€ (8.6 mm), and in the bacteria Enterococcus faecalis in the brand â€œAâ€ (3mm), brand â€œBâ€ (6,1 mm), brand â€œCâ€ (5.6 mm). Virgin Coconut Oil from various merck able to inhibit Staphylococeus aureus and Enterococcus faecalis bacteria.